Nongenetically transmitted disproportionate ventricular septal thickening associated with left ventricular outflow obstruction. - Maron, B J (1979)
Clinical, haemodynamic, and morphological features are described in 2 patients with disproportionate ventricular septal thickening, left ventricular outflow obstruction with systolic anterior motion of the anterior mitral leaflet, and either acquired or congenital heart disease. The disproportionate septal thickening in these patients appeared to be secondary to their underlying cardiac disease rather than a manifestation of genetically transmitted hypertrophic cardiomyopathy. One patient with combined aortic and mitral stenosis had severe systolic anterior motion of the anterior mitral leaflet and a residual large systolic pressure gradient between left ventricle and systemic artery after aortic valve replacement. In this patient the systolic anterior motion was evident in the presence of mitral valve stenosis. The other patient with mild aortic stenosis and a previously repaired coarctation of the aorta also had mild systolic anterior motion and a small subaortic systolic pressure gradient. Hence, these 2 patients demonstrate that disproportionate septal thickening secondary to acquired or congenital heart disease may be associated with left ventricular outflow obstruction and systolic anterior motion of the anterior mitral leaflet.